Pengaruh Latihan MC Kenzie Cervical Untuk Memperbaiki Postur Leher Pada Siswa SMK Brantas karangkates - Agata Sukha Kartika; Fransisa Xaferia Hargiani; Yohanes Deo Fau; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: The human body consists of bones that arrange each other in an orderly manner to support the body. The position of the bones that do not match the shape or anatomy of the normal human body has an influence on human body posture, especially this time for students. One of the problems experienced is a disturbance in the neck, namely FHP (Forward Head Posture) which causes an imbalance in the work of the neck muscles. For students, this condition exacerbates the situation because physiologically there has been a decrease in overall muscle performance. Purpose: The purpose of this study was to determine the effect of Mckenzie Cervical on improving neck posture in students of the Brantas Karangkates Vocational School. To measure the degree of neck flexion in students before and after being given the Mckenzie Cervical exercise and to identify the results of the measurements taken in Boro Blitar Village.Methods: This research is a quasi-experimental research through the use of using data processing, namely using pre- test as data before receiving treatment and post-test after receiving treatment (one group pre-test post-test). Through the presence of pre-test and post-test, the reviewers can obtain objective results in the form of an increase or decrease in results. This research does not require a control group (Rianto A, 2011), this study was carried out to pay attention to the influence of Mckenzie Cervical exercises to improve posture in students before and after being given treatment, the degree of neck posture using the Geniometer in the PhysioMaster application. 36 people with 16 men, 20 women. This group has enough complaints because in their teens the ability of the musculoskeletal system naturally decreases or it could also be caused by other factors that cause complaints.Results: This research is a quasi-experimental research through the use of using data processing, namely using pre- test as data before receiving treatment and post-test after receiving treatment (one group pre-test post-test). Through the presence of pre-test and post-test, the reviewers can obtain objective results in the form of an increase orÂ decrease in results. This research does not require a controlÂ group (Rianto A, 2011), this study was carried out to pay attention to the influence of Mckenzie Cervical exercises to improve posture in students before and after being given treatment, the degree of neck posture using the Geniometer in the PhysioMaster application. 36 people with 16 men, 20 women. This group has enough complaints because in their teens the ability of the musculoskeletal system naturally decreases or it could also be caused by other factors that cause complaints.. Results: which decreased by 6.9444 in the mean pre-test of 13.583 to 6.639 after Mckenzie Cervical. There was a decrease of 6 in the mean and mode, there was also a decrease in the standard deviation of 1.8839. So that we can conclude that Ho is rejected and H1 is accepted where Mckenzie Cercical training has an effect on improving neck posture in students in Boro Blitar Village. The paired samples test shows that the significant value is p <0.05, so there is a significant difference so that H1 can be accepted . Then we can proceed to the next test, namely the bivariate test. The bivariate test shows that the value of r = 0.332 where there is a strong relationship between the two variables, and we can see the value of p = 0.048 which in this case p <0.05 so that H1 is accepted, that Mckenzie Cervical training has an effect on improving posture neck of students inConclusion: From the results of the research that was carried out for 2 weeks and the process of analyzing the data obtained, the researchers concluded that the Mckenzie Cervical training had an influence on improving the neck posture of students in the Boro Blitar Village, where we can find out from the test results and the process during the study. or the improvement in neck posture that students get when doing the McKenzie Cervical exercise is different. This is due to the interest in the research object during the training, as well as the seriousness of the students in doing the Mckenzie Cervical.